Different datum and cartographic projections from Costa Rica: generalities and relations. - Moya-Zamora, Jorge; Cedeño-Montoya, Bepsy (Revista Geográfica de América Central., 2017)
As of the second half of the 20th century, Costa Rica has been implemented and used a series of map projections. The first official map of the country that worked for decades was based on a projection of Lambert, with two contact parallels and defining the so-called northern and southern areas. This national mapping considered -as a reference surface, Clarke ellipsoid 1866, and the coordinates of the points from triangulation chains as a reference framework. In the early 1990s, a project whose main purpose was to provide the country with a new geodetic network based on satellite positioning via GPS was developed. The adjusted coordinates of the vertexes of this network on the WGS84 ellipsoid constituted the basis of datum CR90, whose data were used in generating CRTM90 projection mapping. At the end of that decade, a research project made by Escuela de Topografía, Catastro y Geodesia (ETCG), brought GPS measurements of several national projects, and made the first adjustment of Costa Rican geodetic network within the International Terrestrial Reference Framework (ITRF) 1994 (Dörries and Roldan, 1999) and (Dörries y Roldán, 2004). This new datum was designated as CR98, and it was related to the CRTM98 projection. In the mid-2000s, the measurement of another national geodetic network within ITRF2000 was performed, which constitutes the basis of the official datum of Costa Rica -known as CR05, and the corresponding official projection mapping CRTM05. The different geodetic networks that have been measured in Costa Rica and their corresponding map projections imply having a large amount of geospatial information, from which it is essential to know its metadata in order to be able to project it to the correct plane or to properly transform it. Although it is true that for many practical applications the working scale does not allow displaying a direct effect on the cartographic product, the proper management of information is essential.